Surface activity levels of 7Be, 210Pb, 40K and other atmospheric species and the influence of African air mass intrusions. - Liger-Pérez, Esperanza; Gordo Puertas, Elisa; Dueñas-Buey, Mª Concepción; Cañete-Hidalgo, Sergio Andrés; Cañada, Pedro; Cabello Ganuza, María; Pérez-Martínez, Manuel (My University, 2015)
The high frequency of mineral dust plumes blown across from Africa to the Iberian Peninsula significantly affects dust levels in the atmosphere. Therefore, it is of great interest to analyse and quantify the African dust loading over the region due to the impact it has on air quality. This work presents results from a 2-year sampling campaign carried out to provide information on the frequency and impact of these African dust episodes on the concentrations of radioactive matter and non radioactive matter in the lower atmosphere at this Mediterranean coastal site. Aerosol samples for radiometric measurements were collected at the University of Málaga (36° 43′ 40″ N; 4° 28′ 8″ W) over 3-day periods using a high-volume sampler fitted with square polypropylene filters. All the radiometric measurements were performed by low-level gamma spectrometry with a coaxial-type germanium detector. The identification of African events was confirmed by means of 4-day backward trajectories (at 500, 1500, 3000 m.a.g.l.) computed using the HYSPLIT model and BSC-Dream8b dust images. Higher average concentration values were found for the three radionuclides in the set of samples collected under the influence of African dust events. The correlation patterns of the three radionuclides with meteorological variables and with the concentrations of the other atmospheric species were examined, both on the total set as well as on dusty and non-dusty basis.
Keywords: Isótopos radioactivos; Aire - Contaminación; Atmospheric radionuclides; Aerosols; Back-trajectories; Dust intrusions